Analysis of potential and development strategies for bird's eye chili (Capsicum frutescens) agriculture - Nor Isnaeni Dwi Arista; Dian Novita Susanto (Social Agriculture, Food System, and Environmental Sustainability, 2026)
Background: Batam City, as an industry and service-based metropolitan area, exhibits high dependence on external food supply, reflected in its agricultural sector's contribution of merely 1.45%. This research aims to analyze the potential and formulate a development strategy for bird's eye chili (Capsicum frutescens) as a leading local commodity in Galang and Nongsa Districts to support food security. Methods: This qualitative research with an intrinsic case study strategy utilized secondary data from the Batam City Central Statistics Agency (2021-2025) and SWOT analysis. Findings: The findings reveal complementary potential between the two districts. Galang, with its eight agriculture-based villages, represents an ideal production base, while Nongsa, adjacent to tourism areas and the airport, has the opportunity to become a marketing and agritourism hub. Conclusion: The local market is highly promising for bird’s eye chili, with household expenditure on vegetables at 3.74% and an educated population supportive of technology adoption. However, key challenges include sharp fluctuations in harvested area, land conversion pressure, and inter-island logistics vulnerability. Novelty/Originality of this article: The effective bird's eye chili development requires an integrated strategy: establishing Galang as a certified production center and Nongsa as an agritourism zone, supported by direct market partnerships, digital technology utilization, and policy protection for sustainable agricultural land. This model offers a concrete pathway for economic diversification and food security in an industrial archipelagic region.